25.7k views
0 votes
For g(x) = 12x - 2, evaluate g (1).
A. -1
B. 1
C. 2
D. -2

For g(x) = 12x - 2, evaluate g (1). A. -1 B. 1 C. 2 D. -2-example-1
User Led
by
5.7k points

2 Answers

4 votes

Answer:

Explanation:

To evaluate g(1) for the function g(x) = 12x - 2, you can substitute the value 1 for x in the function:

g(1) = 12(1) - 2

g(1) = 12 - 2

g(1) = 10

Therefore, g(1) = 10. B

User Ttlg
by
6.6k points
3 votes

Answer:

B

Explanation:

g(x) = 12x - 2

g(1/4) = 12(1/4) - 2 ==> plug in 1/4 for x

g(1/4) = 12 * 1/4 - 2

g(1/4) = 12/4 - 2

g(1/4) = 3 - 2

g(1/4) = 1 ==> B